Okultisme Dalam Al-Qur’an : Studi Analisis Relasi Jin dan Manusia dalam Tafsir Al-Munir - Afidah, Ani Nur Afidah (Jawa Timur: Prodi. Ilmu Al Quran dan Tafsir Fakultas Ushuluddin IAI Tarbiyatut Tholabah, 2024)
Occultism, as a magical belief that transcends human reason, is still prevalent in society, as reflected in the practice of witchcraft or black magic. This research examines occultism in the Qur'an, specifically Q.S. Al-Baqarah verse 102, as well as the relationship between jinn and humans. This research uses a qualitative approach with a library research method, analyzing primary sources such as the Qur'an and Wahbah Az-Zuhaili's commentary Al-Munir, as well as relevant secondary sources. The results show that Q.S. Al-Baqarah verse 102 emphasizes the dangers of magic and the disbelief of Satan, as well as the importance of protection from Allah. The practice of occultism involves communication with supernatural beings. As for the relationship between jinn and humans barbarslot, both have the same basic needs and the obligation to worship Allah. This is reinforced by Q.S. Al-Ahqaf verse 29, which describes how the Prophet Muhammad taught the Qur'an to the jinn. These findings contribute to the understanding of the relationship between jinn and humans in the context of occultism, as well as the importance of protection from Allah in facing misleading practices. This research also highlights the urgency of further studies on occultism from religious and social perspectives, as well as its implications for society.